Sustainability of Pension Systems in the Baltic States - Olga Rajevska (Entrepreneurial Business and Economics Review, 2015)
Objective: The objective of the paper is to identify how the concept of sustainability is understood and ensured in the pension systems of Estonia, Latvia and Lithuania; and what implications it brings to the performance of pension schemes. Research Design & Methods: Analysis of various conceptual and methodological approaches to the notion of sustainability of pension systems. Comparative analysis of present pension legislation, as well as preceding stage of pension reforms,  accompanied by a number of numerical models. Findings: The understanding of sustainability is limited by narrow 'fiscal' meaning in Latvia, compared to more a multifaceted concept that includes the principle of social fairness and which can be traced in the logic of Estonian and Lithuanian legislators. Implications & Recommendations: In the long-term, pure financial appreciation of sustainability is misleading, low level of credibility may cripple a financially sound but socially unfair system; the perceived unfairness of redistribution can undermine the public support to, and, therefore, sustainability of pension systems. Contribution & Value Added: The originality of this work lies in studying how differences at policy formulation stage and in the very design of pension schemes influence pension system sustainability in countries with a very similar initial conditions and socio-economic environment.